Social mass gathering events influence emergency medical services call volume - Kienbacher, Calvin Lukas; Herkner, Harald; Alemu, Feven; Rhodes, Jason M.; Al Rasheed, Norah; Aldeghaither, Ibrahem; Barnawi, Esam; Williams, Kenneth Alan (Frontiers in Public Health, 2024)
Background Prior literature suggests that mass gathering events pose challenges to an emergency medical services (EMS) system. We aimed to investigate whether events influence EMS call rates. Materials and methods This study is a retrospective review of all primary response ambulance calls in Rhode Island (US) between January 1st, 2018 and August 31st, 2022. The number of EMS calls per day was taken from the state’s EMS registry. Event data was collected using a Google (Google LLC, Mountain View, CA) search. We used separate Poisson regression models with the number of ambulance calls as the dependent and the social event categories sports, agricultural, music events, and public exhibitions as independent variables. All models controlled for the population at risk and the period of the COVID−19 pandemic. Results are presented as increases or decreases in calls per 100,000 inhabitants from the mean over the study period. Results The mean number of daily EMS calls was 38 ± 4 per 100,000 inhabitants. EMS encountered significantly more missions on days with music events (+3, 95% CI [2; 3]) and public exhibitions (+2, 95% CI [1; 2]). In contrast, days with agricultural events were associated with fewer calls (−1, 95% CI [−1; 0]). We did not find any effect of sports events on call rates. Conclusion Increased ambulance call volumes are observed on days with music events and public exhibitions. Days with agricultural events are associated with fewer EMS calls.